Evaluation of trauma‐induced coagulopathy in the fibrinogen in the initial resuscitation of severe trauma trial. Issue Volume 61:Issue S1 (2021)Supplement (16th July 2021) - Peng, Henry T.; Nascimento, Barto; Rhind, Shawn G.; da Luz, Luis; Beckett, Andrew
Abstract: Background: Coagulopathic bleeding is frequently present after major trauma. However, trauma‐induced coagulopathy (TIC) remains incompletely understood. This laboratory analysis of blood samples derived from our completed trial on fibrinogen in the initial resuscitation of severe trauma (FiiRST) was conducted to evaluate TIC and associated responses to fibrinogen replacement. Study design and methods: We conducted a retrospective evaluation of TIC in 45 FiiRST trial patients based on rotational thromboelastometry (ROTEM), international normalized ratio (INR), and biomarkers for hemostasis and endotheliopathy. Whole blood was analyzed by ROTEM. Plasma was analyzed for INR and biomarkers. Results: Overall, 19.0% and 30.0% of the FiiRST trial patients were coagulopathic on admission defined by EXTEM maximum clot firmness out of the range of 40–71 mm and INR >1.2, respectively. The FiiRST patients showed lower fibrinogen, factor II and V levels, protein C and antiplasmin activities, higher activated protein C, tissue plasminogen activator, d ‐dimer, and thrombomodulin concentrations at admission than healthy controls. Most of the biomarkers changed their activities during 48‐h hospitalization, but were at abnormal levels even 48‐h after admission. The fibrinogen treatment reduced hypofibrinogenemia and increased factor XIII level, but had no significant effects on other biomarkers levels. Limited development of endotheliopathy was indicated by syndean‐1, thrombomodulin, and sE‐selectin. Conclusions: About 19%–30% of the trauma patients in the FiiRST trial were coagulopathic on hospital admission depending on the definition of TIC. Analyses of the TIC biomarkers demonstrated that hemostasis would not return to normal after 48‐h hospitalization, and fibrinogen replacement improved hypofibrinogenemia.